Spansk mad – en illustreret onlineordbog - Gawinski, Birthe (Nordiske Studier i Leksikografi, 2006)
Spanish food – an illustrated online dictionary. The question of equivalence has always created problems for lexicographers when we work with bilingual dictionaries. I have wondered whether information technology might offer a solution to this problem. The question that I have tried to answer is the following: “Can encyclopaedic information including illustrations rectify missing equivalence in bilingual, web-based dictionaries within cultural subject areas?” I have chosen to limit the subject to gastronomy, because this subject has a very culture-specific terminology. The target group of the dictionary is not limited to one particular group. Because of the hypertext structure that allows the user to work at various levels, the dictionary may meet the needs among Danish-speaking people with varying knowledge of Spanish. My conclusion is that the user of an online dictionary will have access to a lot more relevant information using an online encyclopaedic dictionary than it is possible to offer in a printed dictionary.